In Search of Cooperation: An Historical Analysis of Work Organization and Management Strategies - Greenbaum, Joan (DAIMI Report Series, 1988)
During the last decade, literature about work has increasingly focused on the importance of collective communication, tacit knowledge, and group activities. The idea of designing computer support for groupbased work activities, which we loosely call ''cooperative work'', is a useful and challenging one, for it represents a break from design approaches that focused on centralized and bureaucratic systems of communication and control. To get a clearer idea of the meaning of cooperative work. this article will look at historical patterns of world organization and management strategies. It will contrast user-centered concepts of cooperative work, with the idea of seeing cooperative work in the context of democracy in the workplace. The focus on workplace democracy has been a main theme in the Scandinavian systems tradition. The article uses the Scandinavian tradition, with its roots in a Labor Process Approach as a way to analyze the meaning of cooperation for workplace democracy and its implication for the design of computer support.